2020
DOI: 10.4097/kja.20041
|View full text |Cite
|
Sign up to set email alerts
|

Driving pressure guided ventilation

Abstract: Protective ventilation is a prevailing ventilatory strategy these days and is comprised of small tidal volume, limited inspiratory pressure, and application of positive end-expiratory pressure (PEEP). However, several retrospective studies recently suggested that tidal volume, inspiratory pressure, and PEEP are not related to patient outcomes, or only related when they influence the driving pressure. Therefore, this review introduces the concept of driving pressure and looks into the possibility of driving pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
(108 reference statements)
0
15
0
2
Order By: Relevance
“…It is because the tidal volume was different between the two groups, and the tidal volume affects the magnitude of the driving pressure [ 22 ]. Cstat is tidal volume/driving pressure [ 14 ], and there was no difference in Cstat between the PV and CV groups (Fig. 6 ), resulting in no statistical difference in lung ultrasound scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is because the tidal volume was different between the two groups, and the tidal volume affects the magnitude of the driving pressure [ 22 ]. Cstat is tidal volume/driving pressure [ 14 ], and there was no difference in Cstat between the PV and CV groups (Fig. 6 ), resulting in no statistical difference in lung ultrasound scores.…”
Section: Discussionmentioning
confidence: 99%
“…In the PV group, patients were provided with a tidal volume of 8 ml/kg IBW and an intraoperative 6 cmH 2 O PEEP. In the DV group, based on a previous study [ 14 ], PEEP was increased from 5 cm H 2 O to 15 cmH 2 O before titration, with 5 cmH 2 O intervals for recruitment. Each PEEP level was maintained for 4–5 respiratory cycles (< 90 s required).…”
Section: Methodsmentioning
confidence: 99%
“… 10 13 26 P peak is commonly reflected C dyn of the entire respiratory system, 27 and under isovolumetric conditions, C dyn is not only related to the elastic properties of the respiratory system but also resistive elements of the respiratory mechanism such as airway pressure. 13 28 On the other hand, P mean , the average pressure of the respiratory system throughout the inspiratory phase, corresponds to mean alveolar pressure, and an increase in P mean seems to be closely related to increased oxygenation by recruiting collapsed alveoli and reducing shunt. 27 29 30 P mean is one of the most critical factors related to gas exchange and it determines the recruitment of collapsed alveoli and redistribution of alveolar blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study that explored the level of electrical impedance tomography-guided PEEP that minimizes lung collapse and hyperdistention showed that individualized PEEP reduced postoperative atelectasis and improved intraoperative oxygenation. 27 In fact, low tidal volumes and driving pressure, 28 rather than PEEP combined with lung RMs, are known to be responsible for lung protection in the intraoperative period. 7 In this study, we assessed loss of lung aeration during the perioperative period and examined whether a commonly used PV strategy using low tidal volume is associated with more atelectasis compared to CV.…”
Section: Discussionmentioning
confidence: 99%